If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -3x) = 15 (3 * 4 + -3x * 4) = 15 (12 + -12x) = 15 Solving 12 + -12x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -12x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + -12x = 15 + -12 -12x = 15 + -12 Combine like terms: 15 + -12 = 3 -12x = 3 Divide each side by '-12'. x = -0.25 Simplifying x = -0.25
| 1.5x-0.7=0.4(3-5x) | | 2x+11= | | 4+6(3.36-3)=3-5(3.36-4) | | 4h+1=-35 | | 0.04x=0.36 | | 2x^2-7x-54=0 | | 11a+14=-8 | | 3-y=20 | | 2x^2+14x=x^2-45 | | (10x-2)+(8x+4)3= | | 8x-3(4x-5)=-2x-11 | | 8(2x+7)= | | 18+4y-4=17y-13-4y | | 6(x+6)-2= | | 6y=3x+24 | | 2x^2+6x=-18 | | -7n+8=-5n-4 | | 20x-5-16x+2=15x-4-11x+13 | | x+18+2x=-20-2x-27 | | 6x-45=45 | | -14x-20=-12x+120 | | 5x+35=65 | | 17-4x=12+x | | -2(5x-3)+3(4-3x)= | | 0.43+2x=13.6 | | 8y^2-10y-3=0 | | 8x-1=9x+9 | | 5c^2+6=0 | | 10x=62 | | 6y-3=10y+13 | | 2(x+8)=26 | | 4y-14x=1 |